Effects of Digital Score Reporting and Feedback on Students' Learning in Higher Education - Bulut, Okan; Cutumisu, Maria; Aquilina, Alexandra M.; Singh, Deepak (Frontiers in Education, 2019)
Personalized feedback generated via digital score reports is essential in higher education due to the important role of feedback in teaching and learning as well as in improving students’ performance and motivation in such educational settings. This study introduces and evaluates ExamVis, a novel and engaging digital score reporting system that delivers personalized feedback to students after they complete their exams. It also presents the results of two empirical studies employing hierarchical linear regressions in which 776 pre-service teachers took two midterms and a final exam, receiving a digital score report with personalized feedback after each exam and having the option to review each of the score reports. Study 1 found that reviewing short reports (with visual feedback given immediately after an exam) and extended reports (with visual and written feedback given after all students completed the exam) significantly predicted students’ final exam scores above and beyond their midterm exam scores. Study 2 found that students who were provided with only extended digital score reports outperformed on the final exam those who had access to both short and extended digital score reports. Implications for designing digital score reports with personalized feedback that have a positive impact on student performance are discussed.